Nuclear interactions and multiple coulomb scattering at volume reflection - Bondarenco, M.V. (Вопросы атомной науки и техники, 2012)
For volume reflection of charged particles governed by the continuous potential of atomic planes in a bent crystal, we calculate the probability of a nuclear interaction. It is found to differ from the corresponding probability in an amorphous target by an amount proportional to the crystal bending radius and the particle mean deflection angle, independently of the shape of the interplanar continuous potential. That result is also applied to the description of the final beam angular divergence owing to the multiple Coulomb scattering. The theoretical predictions are compared with the results of recent experiments.